IMPLEMENTASI SURAT EDARAN DIRJEN BIMAS ISLAM NOMOR P-005/DJ.III/HK.00.7/10/2021 TENTANG MASA 'IDDAH ISTRI DAN SUAMI DI KUA SE KOTA TASIKMALAYA TAHUN 2022-2023 - Fahrul; Gunadi (Program Studi Hukum Keluarga Islam, 2024)
Iddah means a calculation or waiting period for a wife who has been divorced by her husband, but in the Circular Letter of the Director General of Islamic Guidance Number: P-005/Dj.III/Hk.007/10/2021 published in 2021 which requires a husband to also wait for his ex-wife's iddah period. The purpose of this study is to determine the background, legal position and sanctions of the circular letter of the Director General of Islamic Guidance and its application in the Tasikmalaya City KUA. This research uses qualitative methods with observation and interview data collection techniques. The results of this study, first, the background of the issuance of this Circular Letter there are 3 things, namely the ineffectiveness of the 1979 Circular Letter, the potential for covert polygamy, and the procedure for fracturing marriage. Second, the position of this circular letter is not included in the laws and regulations and is contrary to the UUP and KHI so that there are no special sanctions. Third, the implementation carried out by the Tasikmalaya City KUA has been socialized to every former husband who will remarry in the iddah period of his ex-wife. The impact of this Circular Letter is that many people still do not understand this, but after the socialization by the KUA, the community understands and follows the existing regulations.